Chinese senior primary school students’ civic literacy and its affecting factors - Yao, Yao; Cai, Lian-Yu; Oubibi, Mohamed (Frontiers in Psychology, 2022)
Introduction Measuring the current situation of civic literacy of senior primary school students (grade 5 and 6) and exploring its affecting factors is the basis for improving the effectiveness of civic education at this stage. Methods The research developed the measurement questionnaire through item analysis, exploratory factor analysis, and other methods. It then was distributed nationwide online through stratified and cluster sampling, through which 1642 valid questionnaires were finally collected. The study took mean analysis, difference analysis, correlation analysis, and regression analysis. Results The statistical results eventually showed the civic literacy of China’s senior primary school students is, on the whole, at a comparatively high level. Chinese scholars Zhang Jiajun and Xu Jiao combined the particularity of civic literacy to divide it into four dimensions and the performance of the four dimensions of civic literacy is revealed to be: civic affection > civic cognition > civic competence > civic behavior. Further, a significant difference exists in students’ civic literacy by gender (girls’ civic literacy scores M = 299.53, SD = 28.15, N = 785 are significantly higher than the boys’ civic literacy scores M = 293.18, SD = 32.25, N = 857, t = 4.263, p < 0.01), and whether they have been student leaders (those students who served as student leaders M = 304.33, SD = 26.57, N = 649 those who were not student leaders M = 290.86, SD = 31.69, N = 984, t = 9.272, p < 0.01). Conclusion The family social economic status (SES) and school education were significantly positively correlated with students’ civic literacy. Based on this, primary schools should implement educational compensation for cultivating civic literacy among the socioeconomically disadvantaged senior primary school students and carry out civic education according to the specific conditions of civic literacy of senior students.